Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Balai Bahasa Provinsi Aceh - Ayi Satria Yudha; Nasri Zarman; Ferdi Nazirun Sijabat; meliana meliana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2022)
Motivation and work discipline are an important part of achieving good performance. This study aims to analyze the influence of work motivation and discipline on employee performance at the Language Center of Aceh Province. This research is a survey, the number of respondents is 31 people. Data analysis using statistical analysis models of correlation and multiple regression. The partial test results show that work motivation influences employee performance with a value of 0.429 or 42.9%. Work discipline affects employee performance with a value of 0.556 or 55.6%. After the t test shows that work motivation has an effect on employee performance of tcount2,151 > ttable1.645 and p value 0.040 < 0.05 means significant. Work discipline affects employee performance with a value of tcount2,552 > ttable1.645 and p value 0.016 < 0.05. The results of the analysis show that simultaneously there is an influence between work motivation and work discipline on performance of 0.798 or 79.8% and 0.637 or 63.7% is influenced by other variables. After doing the F test, the number F is obtainedcount(24,537) > Ftable(3.070) and test the significance that the p value is 0.000 < p which is set at 0.05. The conclusion of the study is that motivation and discipline partially and simultaneously have a positive and significant effect on employee performance at the Aceh Province Language Center.